Emotions and (Allegedly) Arational Actions - Salomone-Sehr, Jules (Les ateliers de l'éthique / The Ethics Forum)

(untitled) (Centre de recherche en éthique (CRÉ), 2024)
I discuss Christine Tappolet's treatment of so-called arational actions (chapter 8). Brought to philosophical attention by Rosalind Hursthouse, arational actions are actions done simply because we are in the grip of an emotion (as when we leap up to reach for leaves out of joy). I argue that certainly many instances of so-called arational actions are in fact rational.